Annular Pancreas.: Four Cases - de Mattos, Alfredo; Chizzola, Manlio; Correa, Alberto; Maquieira, Gonzalo; Chavarría, Oscar (Cirugía del Uruguay, 1981)
Discussion of pathogenesis of annular malformation, the most accepted theo·ry being that of earfy attachment of duodenal outline to anterior wall of duodenum.